Transduser Arus Bolak-Balik Menggunakan Kumparan Rogowski - Budhi Anto; Andri Saputra (UIN Sultan Syarif Kasim Riau, 2012)
This paper presents an attempt to design and make a rogowski coil together with its signal conditioning circuit for alternating current measurement. The induced voltage between rogowski coil ends is connected to active integrator circuit to yield voltage signal that is linear corresponding with the measured current. The output of integrator circuit is amplified its level before rectified using precision rectifier circuit. The output of precision rectifier is filtered using capacitor before connected to analog input port of ATMEGA8535 microcontroller. Microcontroller performs data acquisition of the signal, processes it and sends information of the rms value of the measured current to an LCD display. A test with 0.5 class moving-iron type amperemeter as a comparison shows that for measurement of alternating current from 0 to 5 amperes, the maximum value of error measurement is 2.5%.Keywords: rogowski coil, active integrator, precision rectifier, ATMEGA8535 microcontroller